The Clinicopathological Features of Epithelioid Undifferentiated Sarcoma with TFE3 Amplification with One Case Report - Lang, Yuejiao; Li, Xiaojuan; Chen, Shaoyu; Xiang, Pei; Han, Anjia (Archives of Clinical and Medical Case Reports, 2021)
Herein, we first reported a case of undifferentiated sarcoma with epithelioid features harboring TFE3 amplification. A 66-year-old woman with a history of chronic lymphocytic leukemia and chemotherapy presented with a 4 cm palpable nodule in the left lower leg. Microscopically, the large epithelioid tumor cells with remarkable pleomorphism and the small round tumor cells intermingled with each other in a diffuse sheet or a hemangiopericytoma-like vascular growth pattern. Atypical mitotic figures and lymph node metastasis were found while tumor necrosis was absent. Immunohistochemically, the tumor was positive for vimentin, TFE3, and CD34. TFE3 gene amplification was identified by fluorescence in situ hybridization. The patient was alive and well without recurrence or metastasis for 12 months after tumor resection. The tumor should differentiate from PEComa, alveolar soft part sarcoma, epithelioid sarcoma, epithelioid angiosarcoma, and epithelioid rhabdomyosarcoma.